Acute Disseminated Encephalomyelitis and Acute Encephalitis Following Vaccination Against SARS-CoV-2: Two Case Reports and Review of Literature - Weidauer, Stefan; Zeitz, Anne; Tafreshi, Mona; Hattingen, Elke; Arendt, Christophe (Fortschritte der Neurologie · Psychiatrie, 2023)
The spectrum of severe neurological complications following COVID-19 vaccination includes cerebrovascular events, inflammatory diseases of the CNS, cranial and peripheral nerve involvement and muscle affections. Post-vaccinal acute disseminated encephalomyelitis (ADEM) and acute encephalitis are rare. We report on a patient suffering from acute encephalitis and another with post-vaccinal monophasic ADEM. Beside imaging features typical for acute autoimmune associated inflammation, cranial MRI disclosed also transient haemorrhagic signal alterations in some cerebral lesions. To our best knowledge, this has not been mentioned before in literature. Competing causes were excluded by extensive laboratory investigations including serial CSF analysis. In line with the literature, repeated iv high-dosage corticosteroid therapy resulted in impressive improvement of neurological symptoms in both patients.
Keywords: acute disseminated encephalomyelitis; encephalitis; vaccination; SARS-CoV-2; magnetic resonance imaging